Probabilistic puzzle: toward a solution of Goldbach’s conjecture? - D’Amico, Rosario (Journal of Mathematical Economics and Finance; Vol 9 No 2 (2023): JMEF, Volume IX, Issue 2(17), Winter 2023, 2023)
This paper aims to provide a set of considerations that allow us to see a possible solution to the problematic issue of Goldbach’s “strong” conjecture, which amounts to asserting that any even natural number greater than 2 can be written as the sum of two prime numbers that are not necessarily distinct. This is by adopting a probabilistic method by far easier attempts than the classical ones already present in literature.